2012
DOI: 10.1134/s1064229312040072
|View full text |Cite
|
Sign up to set email alerts
|

The formation of water-stable coprolite aggregates in soddy-podzolic soils and the participation of fungi in this process

Abstract: The water stability of soil and coprolite aggregates in soddy podzolic soils and the participation of fungi in the formation of water stable aggregates from earthworm (Aporrectodea caliginosa) coprolites were assessed. The water stability of the soil and coprolite aggregates in the soils increased in the following sequence: potato field-mown meadow-mixed forest. The fungal mycelium reserves increased in the same sequence. The water stability of the coprolite aggregates of Aporrectodea caliginosa inhabiting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…There were substantial differences (P ≤0.05) in SOC in the WSA (mainly in WSA mi ) between the fertilized treatments and the non-fertilized treatment. Tisdall and Oades (1980) and Kurakov and Kharin (2012) found greater concentrations of organic C in macroaggregates than in micro-aggregates and suggested that it is due to decomposing roots and hyphae within macro-aggregates. Elliott (1986) suggested that macroaggregates have elevated C concentrations because of the organic matter binding micro-aggregates into macroaggregates and that this organic matter is "qualitatively more labile and less highly processed" than the organics stabilizing micro-aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…There were substantial differences (P ≤0.05) in SOC in the WSA (mainly in WSA mi ) between the fertilized treatments and the non-fertilized treatment. Tisdall and Oades (1980) and Kurakov and Kharin (2012) found greater concentrations of organic C in macroaggregates than in micro-aggregates and suggested that it is due to decomposing roots and hyphae within macro-aggregates. Elliott (1986) suggested that macroaggregates have elevated C concentrations because of the organic matter binding micro-aggregates into macroaggregates and that this organic matter is "qualitatively more labile and less highly processed" than the organics stabilizing micro-aggregates.…”
Section: Resultsmentioning
confidence: 99%
“…stimulates the development of their populations. The water stability of coprolite aggregates of Aporrectodea caliginosa is 2-2.5 times higher than that of soil aggregates of the same size [99]. The coprolite aggregates contain more clay particles and organic matter and less sand IOP Publishing doi:10.1088/1755-1315/1049/1/012062 13 than the surrounding soil, because earthworms selectively absorb smaller particles and organic residues.…”
Section: Discussionmentioning
confidence: 98%
“…To distinguish in this case the cause from the effect is extremely difficult, because suitable for earthworms are conditions with the predominance of meso-aggregates. The earthworms form zoogenic aggregates (coprolites), which are also mesoaggregates in size [99]. We hypothesized that earthworms, in the case of their influence, should explain that part of the variability of soil aggregate structure that factors of other origin do not explain.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregate stability is affected by soil intrinsic factors such as the strength of electrolytes, types of exchangeable cations (Paradelo et al, 2013), type and abundance of clay minerals (Bronic and Lal, 2005), content of carbonates (Vaezi et al, 2008), SOM (Saha et al, 2011;Simansky and Jonczak, 2016), and geochemical barriers such as Fe, Mn and Al oxides and hydroxides (Barthes et al, 2008). All of these factors depend on the climate conditions, soil formation processes (wet-dry and freeze-thaw cycles), biological factors and soil management practices (Balashov and Buchkina, 2011;Kurakov and Kharin, 2012). It has been already observed that aggregate stability increases with the content of SOM (Kodesova et al, 2015;Simansky and Jonczak, 2016).…”
Section: Introductionmentioning
confidence: 99%